Pharmacokinetics and tissue distribution study of clevidipine and its primary metabolite H152/81 in rats. (8th August 2017) - Wang, Yan; Zhao, Lanting; Li, Tengfei; Yang, Wen; Li, Qian; Sun, Luning; Ding, Li
Abstract: This present study was designed to investigate the pharmacokinetic profiles and tissue distribution characteristics of clevidipine and its primary metabolite H152/81 in rats following a single intravenous administration of clevidipine butyrate injectable emulsion. For this study, a sensitive and selective liquid chromatography–tandem mass spectrometry (LC–MS/MS) method was established and validated for the simultaneous quantitation of clevidipine and H152/81 in rat whole blood and various tissues. A Hedera ODS‐2 column with two gradient elution programs was employed for the troubleshooting of matrix effect on the detection of analytes among different biological samples. The experimental data showed that clevidipine represented quick elimination from blood with a half‐life of about 4.3 min and rapid distribution in all of the investigated tissues after administration; the highest concentration of clevidipine was found in the heart whereas the lowest concentration was detected in the liver. In addition, clevidipine was almost undetectable in most tissues except for heart and brain at 90 min post‐dosing, suggesting that there was no apparent long‐term accumulation in rat tissues. For H152/81, the peak concentration of 3714 ± 319 ng/mL occurred at 0.129 ± 0.048 h, the half‐life was 10.08 ± 1.45 h and area under the concentration–time curve was 42091 ± 3812 ng h/mL after drug administration. In addition, H152/81 was found at significant concentration levels in all tissues, in descending order of lung, kidney, heart, liver, spleen and brain at each time point. The results of current study offer useful clues for better understanding the distribution and metabolism of clevidipine butyrate injectable emulsion in vivo .